Instructional leadership in centralised systems: evidence from Greek high-performing secondary schools - Kaparou, Mary; Bush, Tony (Taylor & Francis, 2015)
This paper examines the enactment of instructional leadership (IL) in high-performing secondary schools (HPSS), and the relationship between leadership and learning in raising student outcomes and encouraging teachers’ professional learning in the highly centralised context of Greece. It reports part of a comparative research study focused on whether, and to what extent, IL has been embraced by Greek school leaders. The study is exploratory, using a qualitative multiple case design to examine two HPSS in Athens. The research design involved a qualitative approach using several different methods, including semi-structured interviews with school principals, deputy heads, subject teachers and subject advisers, plus observation of leadership practice and meetings and scrutiny of relevant policy documents. The findings show that IL is conceptualised as an informal collaborative leadership practice, interwoven with the official multi-dimension role of Greek principals and their ‘semi-IL’ role. In the absence of official IL ‘actors’, teachers’ leadership has been expanding.